(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This paper discusses the major themes in one of the Hemingway’s enduring works, The Old Man and the Sea. It is a deceptively simple story, told with great power, of a decrepit Cuban fisherman who struggles through the most difficult patch in his life—unlucky and his supreme ordeal with an unrelenting, excruciating fight with a giant marlin far out into the Gulf Stream. Though short and simple, this work is not only dramatic but also propagates that a mere human can overcome struggles in life. In very contemporary terms, Hemingway retells the courage-in-the-face-of-defeat theme, personal triumph from loss. Hemingway tells the tale in simple yet powerful language about an old Cuban fisherman fighting his biggest fight at the worst period of his life — unlucky and his supreme ordeal with a giant marlin far out in the Gulf Stream. Though short and simple, this work teems not only with drama but also with the introspection that a simple man can overcome such insurmountable odds in life. In a resolutely contemporary reworking, Hemingway captures the classic theme of courage in the face of defeat, of personal triumph won from loss.